Sustainable Cultural Tourism Innovation: Cow Cart in Palbapang Village - Dita, Apro; Pinontoan, Nexen Alexandre; Jati, Rocky Prasetyo; Jatisidi, Artyasto (Jurnal Mantik, 2024)
This study investigates the sustainable cultural tourism innovation using cow carts in Palbapang Village, Yogyakarta. The background highlights the importance of integrating sustainability into tourism development to preserve cultural and environmental heritage. A qualitative approach was employed, involving in-depth interviews, participatory observation, and document analysis to gather comprehensive data from stakeholders such as cow cart owners, tourism managers, tourists, and local residents. The findings indicate that the cow cart initiative is well-received by the community, enhancing local pride and providing economic benefits by boosting local small and medium enterprises (SMEs). The initiative also reduces environmental impact by minimizing reliance on motor vehicles and promoting waste management and nature conservation. The dis-cussion emphasizes the importance of community participation and government support in im-proving infrastructure and training to ensure high-quality services. The study concludes that cow cart tourism effectively promotes sustainable cultural tourism, preserving cultural heritage while fostering economic growth and environmental conservation. This model demonstrates how tra-ditional practices can be integrated with modern tourism demands to achieve long-term sus-tainability